2021
DOI: 10.1002/eji.202048777
|View full text |Cite
|
Sign up to set email alerts
|

The role of cGAS/STING in intestinal immunity

Abstract: The gastrointestinal tract is a highly complex microenvironment under constant interaction with potentially harmful pathogens. Inflammatory bowel disease (IBD) is an archetypical inflammatory disease, in which the intestinal epithelium, defective autophagy, endoplasmic reticulum stress and dysbiosis play a key role. Although no risk‐mediating gene variants of STING (TMEM173) have been identified so far, several seminal findings have elucidated a novel understanding of STING in the context of acute and chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 151 publications
(259 reference statements)
0
19
0
Order By: Relevance
“…Our work demonstrated that the cGAS-STING-type I IFN signaling axis is critical for the regulation of egg granuloma formation in the liver of schistosome-infected mice. Notably, the cGAS-STING pathway has been implicated as being critical for the regulation of the homeostasis of intestinal immunity [ 41 44 ]. Moreover, the intestine is an important organ for the deposition of eggs [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our work demonstrated that the cGAS-STING-type I IFN signaling axis is critical for the regulation of egg granuloma formation in the liver of schistosome-infected mice. Notably, the cGAS-STING pathway has been implicated as being critical for the regulation of the homeostasis of intestinal immunity [ 41 44 ]. Moreover, the intestine is an important organ for the deposition of eggs [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMEM173, the gene that codes for STING, has been found to be hypomethylated in the GI epithelium of pediatric IBD patients, which could lead to overexpression and overactivity of STING in IECs from IBD patients ( Howell et al, 2018 ). In support of this theory, IBD patients express a wide variety of IFN-regulated genes (IRGs) with higher IFN signatures associated with therapeutic failure ( Coskun et al, 2013 ; Andreou et al, 2020 ; Wottawa et al, 2021 ). A recent paper further links cGAS and inflammsome signalling to colitis ( Ma et al, 2020 ).…”
Section: Lps-independent Activators Of Caspases-4 and -5mentioning
confidence: 97%
“…Recently, it has been found that excessive STING signaling can disrupt calcium homeostasis and render T cells hyperresponsive to ER stress, which may cause prolonged activation of UPR and ER stress. 47 However, the long-term activation of UPR is associated with many pathologies, including metabolic diseases (eg, type 2 diabetes), autoimmune disease (eg, UC), and cancer. Notably, UPR constitutes a highly conserved and intricately regulated group of pathways which aim to initially rebuild homeostasis by stimulating genes involved in protein folding and antioxidant mechanisms.…”
Section: Apoptosis and Er Stressmentioning
confidence: 99%